Foliar Uptake of Toxic Metals Bound to Airborne Particulate Matter in an Urban Environment - Triratnesh Gajbhiye; Sudhir Kumar Pandey; Ki-Hyun Kim (Aerosol and Air Quality Research)
Abstract In this research, the foliar uptake patterns of three toxic metals (Pb, Cd, and Cu) bound to airborne particulate matter (PM) were investigated using two evergreen tree species (Senna siamea and Alstonia scholaris) at six different locations (two residential, traffic, commercial, and industrial) plus one control site in a subtropical urban environment. The concentrations of Pb, Cd, and Cu were measured from foliar dust, leaf, road dust, and soil samples collected from the target sites over two consecutive years. Their temporal variations in leaves were examined at monthly, seasonal, and annual scales. The data were evaluated statistically by One-way Analysis of variance ANOVA and correlation analysis along with enrichment factor (EF). There were significant variations on the monthly as well as the seasonal basis. Accordingly, PM-bound toxic metals in leaves come from an airborne route. In addition, leaves of S. siamea showed a moderately improved accumulation pattern relative to A. scholaris. This study suggests that these plants can be used efficiently as basic tools to assess the pollution and associated behavior of PM-bound toxic metals in an urban environment.